Chemical modification and structural rearrangements of polyketone‐based polymer membrane. Issue 44 (21st July 2017) - Ataollahi, Narges; Girardi, Fabrizio; Cappelletto, Elisa; Vezzù, Keti; Di Noto, Vito; Scardi, Paolo; Callone, Emanuela; Di Maggio, Rosa
ABSTRACT: Alternating polyketones constitute a very interesting class of polymers, which can be modified for the preparation of functional polymers. The chemical modification of polyketone using 1, 2‐diaminopropane was used to prepare a conductive membrane. This paper is focused on the synthesis and structural rearrangements of polyamine for preparing anion‐exchange membranes by the solvent casting technique. According to the Paal‐Knorr mechanism, 1, 4‐dicarbonyl of polyketone reacts with 1, 2‐diaminopropane to form a pyrrole ring along the polyketone backbone. In addition, the so‐modified polyamines can undergo structural rearrangements to form N‐substituted pyrrole crosslinked with dihydropyridine units. The conversion degree and the N content are quite low. The pathway reactions have been proposed on the basis of 1 H‐NMR, ultraviolet–visible, and Fourier transform infrared results. Scanning electron microscopy, differential scanning calorimetry, and X‐ray diffraction techniques were used to study the morphological, thermal, and structural characteristics of the modified polyketone, as well as the correspondoing membrane. The experimental results indicated that the membrane is a potential candidate for energy conversion technology. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45485. Abstract :